Cyclopentadienyl, indenyl and bis(cyclopentadienyl) titanium imido compounds - Dunn, S; Robson, D; Mountford, P (1997)
The titanium tert-butyl imido compounds [Ti(NBut)Cl2(NC5H4R-4)n] (R = H, n = 2 or 3; R = But, n = 2) have been found to be entry points to the half-sandwich η5-cyclopentadienyl derivatives [Ti(η5-C5R′4R″)(NBu t)Cl(NC5H4R-4)] (R = But, R′ = R″ = H or Me; R = H, R′ = H, R″ = H, Me or Pr1; R = H, R′ = Me, R″ = Me, Et or C4H7), the η5-1,2,3-trimethylindenyl species [Ti(η5C9H4Me3)(NBu t)Cl(NC5H4But-4)] and the bis(η5-cyclopentadienyl) compound [Ti(η5-C5H5)2(Nbu t)(NC5H5)], the crystal structure of which has been determined. The complex [Ti(η5-C5H5)(NBut)Cl(NC 5H5)] readily loses pyridine under vacuum in the solid state to form the binuclear complex [Ti2(η5-C5H5) 2(μ-NBut)2Cl2]. Treatment of [Ti(η5-C5Me4R)(NBut)Cl(NC 5H5)] (R = Me or Et) with Na[C5H5] gives the corresponding mixed-ring sandwich derivatives [Ti(η5-C5H5)(η5-C 5Me4R)(NBut)Cl(NC5H5)]. Addition of Li[C9H7] to [Ti(η5-C5H5)(NBut)(Cl(NC 5H5)] gave the η5-cyclopentadienyl, η3-indenyl mixed-ring analogue [Ti(η5-C5H5)(η3-C 9H7)(NBut)(NC5H5)]. The complex [Ti(η5-C5H5)2(NBu t)(NC5H5)] undergoes a room-temperature cyclopentadienyl ligand-redistribution reaction with [Ti(NBut)Cl2(NC5H5)2] forming [Ti(η5-C5H5)(NBut)Cl(NC 5H5)] in quantitative yield. Variable-temperature NMR spectra for the half-sandwich complexes show that the co-ordinated pyridine exchanges with free pyridine via an associative mechanism. The compound [Ti(η5-C5H5)(η5-C 5Me4Et)(NBut)(NC5H5)] is also fluxional and exhibits reversible pyridine dissociation at higher temperatures and restricted rotation about the Ti-N (pyridine) bond at lower temperatures.